2023
DOI: 10.1200/jco.2023.41.16_suppl.5015
|View full text |Cite
|
Sign up to set email alerts
|

A prospective trial of apalutamide and abiraterone acetate plus prednisone in Black and White men with metastatic castrate-resistant prostate cancer.

Abstract: 5015 Background: Abi Race was the first prospective parallel cohort study of abiraterone acetate plus prednisone (AAP) in Black and White men with metastatic castrate-resistant prostate cancer (mCRPC) and demonstrated greater prostate-specific antigen (PSA) response, time to PSA progression (TTP) and toxicity rates among Black patients (pts). We designed the PANTHER trial to estimate clinical outcomes among Black and White pts with mCRPC treated with apalutamide, abiraterone, plus prednisone. Methods: This pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“… 48 More recently, early results from the PANTHER trial, suggest Black men with mCRPCa also have a better response to combined abiraterone and apalutamide [an AR receptor inhibitor] with prednisolone than White men. 49 The efficacy of these treatments in other racial groups requires further study.…”
Section: Precision Medicine and Its Potential Benefits In Alleviating...mentioning
confidence: 99%
“… 48 More recently, early results from the PANTHER trial, suggest Black men with mCRPCa also have a better response to combined abiraterone and apalutamide [an AR receptor inhibitor] with prednisolone than White men. 49 The efficacy of these treatments in other racial groups requires further study.…”
Section: Precision Medicine and Its Potential Benefits In Alleviating...mentioning
confidence: 99%
“…Despite the large sample size, and the racial disparities in prostate cancer where Black men carry the greatest burden in both incidence and mortality, no analyses were conducted by race due to inadequate representation. Recent studies have underscored the significance of having diverse representation in the studies, noting racial differences that would not be observed without adding a racial equity lens to their research questions and recruitment strategies that allow for race and ethnic analyses [13][14][15][16]. For example, a recent study explored the effects of a novel combination of hormonal therapies, Apalutamide and Abiraterone plus prednisone in patients with castrate-resistant prostate cancer and hypothesized that Black men may benefit more than White men [13].…”
Section: Introductionmentioning
confidence: 99%